Do We Belittle Essential Tremor by Calling It a Syndrome Rather Than a Disease? Yes - Lenka, Abhishek; Louis, Elan D. (Frontiers in Neurology, 2020)
Essential tremor (ET) is among the most prevalent neurological diseases. Appreciation in recent years of a richer tremor phenomenology, additional motor and non-motor features, variability in the natural course of tremor, associations with a host of other neurological conditions, and etiological and pathophysiological heterogeneity, has resulted in general awareness of the clinical richness of ET. Along with this evolving view of ET have surfaced several conundrums regarding nomenclature. One of these is whether ET should be labeled a “syndrome” or “disease”. Here, we revisit the classical definitions of “syndrome” and “disease”, and discuss ET in this context. Considering the characteristics of "disease" and "syndrome", and evaluating the characteristics of ET, it seems to fit more into the "disease" construct. There are several reasons: there is considerable knowledge of the underlying etiologies and pathophysiology of ET, in numerous studies ET has been linked with other neurological conditions, the condition is progressive and deteriorative, and therapeutic approaches are grounded in an understanding of disease mechanisms and its associated neuroanatomy. Moreover, the etiological-pathological-clinical heterogeneity suggests that ET should be regarded as a “family of diseases” more appropriately termed “the essential tremors”. This nomenclatural issue is not a mere matter of words; public health implications are numerous. A condition with the label “syndrome” may not be recognized as a serious problem, maybe plagued by diminished public awareness, and may not garner funds for research that a condition with the label “disease” or “diseases” would. ET should be regarded as a family of diseases.